In search of Adonis: marriage strategies and gender identity in Greek transnational migration - Panagakos, Anastasia (The Greek Review of Social Research, 2003)
Transnational migration, or the circular pattern of mobility between two or more nation-states, has been a relatively new phenomenon studied by social scientists. Focusing mainly on household economics and social networking, scholars are only now accounting for the effects of transnational migration on gender identity or marriage. Using the case of the Greek diaspora, this paper explores how transnational migration itself is used as a marriage strategy among young Greek Canadian women who travel to Greece in search of new lifestyles and potential marriage partners. I argue that the imagining of Greece as the ancestral homeland is realized through satellite television, travel, Internet and other forms of rapidly changing communications by creating a sense of belonging that transcends spatial and temporal distances. The search for an idyllic lifestyle and spouse has implications for how gender identity is performed and constrained by social conventions as individuals move between two different nation-states and two different gender systems. I address what «marriage strategies» constitute in the context of a globally mobile Greek population, and how women, traditionally viewed as a commodity in marriage exchange, utilize education and economic success to become decision makers in their marital choices.